Fatty acid and retinol-binding protein: Unusual protein conformational and cavity changes dictated by ligand fluctuations - Barletta Roldan, Patricio German (2019)
Lipid-binding proteins (LBPs) are soluble proteins responsible for the uptake, transport, and storage of a large variety of hydrophobic lipophilic molecules including fatty acids, steroids, and other lipids in the cellular environment. Among the LBPs, fatty acid binding proteins (FABPs) present preferential binding affinities for long-chain fatty acids. While most of FABPs in vertebrates and invertebrates present similar β-barrel structures with ligands accommodated in their central cavity, parasitic nematode worms exhibit additional unusual α-helix rich fatty acid- and retinol-binding proteins (FAR). Herein, we report the comparison of extended molecular dynamics (MD) simulations performed on the ligand-free and palmitic acid-bond states of the Necator americanus FAR-1 (Na-FAR-1) with respect to other classical β-barrel FABPs. Principal component analysis (PCA) has been used to identify the different conformations adopted by each system during MD simulations. The α-helix fold encompasses a complex internal ligand-binding cavity with a remarkable conformational plasticity that allows reversible switching between distinct states in the holo-Na-FAR-1. The cavity can change up to one-third of its size affected by conformational changes of the protein-ligand complex. Besides, the ligand inside the cavity is not fixed but experiences large conformational changes between bent and stretched conformations. These changes in the ligand conformation follow changes in the cavity size dictated by the transient protein conformation. On the contrary, protein-ligand complex in β-barrel FABPs fluctuates around a unique conformation. The significantly more flexible holo-Na-FAR-1 ligand-cavity explains its larger ligand multiplicity respect to β-barrel FABPs.